Nanocomposites films based on soy proteins and montmorillonite processed by casting - Echeverría, Ignacio (2014)
In this work the effect of montmorillonite (MMT) addition to soy-protein-based films on the physicochemical properties of the resulting nanocomposites was studied and the structure–function relationship of these materials and the changes in phase structures, due to different interactions among the material components were analyzed. Flexible nanocomposite films consisting in a soy-protein (SP) matrix supplemented with different concentrations of montmorillonite (MMT) up to 10 g/100 g of SP were prepared by the casting technique. The resulting films were homogeneous, yellowish, and transparent and indistinguishable visually from films of pure protein. The process used for film formation—involving mechanical agitation and ultrasonication, in combination with the intrinsic affinity of MMT for the SPs—favors the dispersion of the clay so as to reach a high degree of intercalation into the protein matrix with consequent exfoliation of the layers of MMT among the proteins (verified by both transmission electron microscopy and X-ray diffraction). The efficient dispersion and distribution of the MMT laminas within the films generated a significant strengthening of the nanolayer that was evident in the observed resistance to breakage; modulation of elasticity; and decrease in extension, moisture content, solubility, and permeability to water vapor. In the presence of MMT, the disulfide bridges in the SPs play a critical role in the stabilization of the protein matrix, whereas in the films composed of proteins alone the residues capable of participating in hydrogen bonding would be involved in other types of highly stabilizing interactions.